PARADIGMA BARU PENDIDIKAN ISLAM KONTEMPORER DI INDONESIA - Zahra Hana Fadhilah; Hudaidah Hudaidah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2021)
The purpose of writing this article is to provide a comprehensive overview of Indonesia's Contemporary Islamic Education dynamics from madrasah, pesantren, diniyah to Islamic universities are analytically accompanied from different viewpoints. Not only those related to national education, but also to political, social and cultural factors in Indonesia, which use as a part of the consideration to view education in Indonesia. The educational landscape, both public and Islamic education in Indonesia, has continued uneasily in its long way to survive until now. After struggling with a long marginalization and backwardness, Islamic education still strives and creates a new paradigm. This study uses descriptive research methods that analyzed Indonesia's contemporary Islamic Education paradigm. The data is obtained through a validation process of the duplicate article titles found in the February-March 2021 period. Current education must adapt to technological development and time development. Hence, it requires global expansion of the education system to answer various global challenges and needs.